2013
DOI: 10.1093/ageing/afs197
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sarcopenia in community-dwelling older people in the UK using the European Working Group on Sarcopenia in Older People (EWGSOP) definition: findings from the Hertfordshire Cohort Study (HCS)

Abstract: Introduction: sarcopenia is associated with adverse health outcomes. The aim of this study was to describe the prevalence of sarcopenia in community-dwelling older people in the UK using the European Working Group on Sarcopenia in Older People (EWGSOP) consensus definition.Methods: we applied the EWGSOP definition to 103 community-dwelling men participating in the Hertfordshire Sarcopenia Study (HSS) using both the lowest third of dual-energy X-ray absorptiometry (DXA) lean mass (LM) and the lowest third of sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
236
5
21

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 334 publications
(279 citation statements)
references
References 31 publications
17
236
5
21
Order By: Relevance
“…Epidemiological data for discordance in sarcopenia prevalence between older men and women have been conflicting (Landi et al 2012;Patel et al 2013;Lee et al 2013). Several studies had suggested differential sexspecific rate of absolute muscle loss, being greater in men than in women, which could not be attributed merely to the larger initial muscle mass in men (Payette et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data for discordance in sarcopenia prevalence between older men and women have been conflicting (Landi et al 2012;Patel et al 2013;Lee et al 2013). Several studies had suggested differential sexspecific rate of absolute muscle loss, being greater in men than in women, which could not be attributed merely to the larger initial muscle mass in men (Payette et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…• 4.6% of men and 7.9% of women with a mean age of 67 in an English cohort study were diagnosed with sarcopenia [25] • Duchenne muscular dystrophy affects 1 in 3500 males worldwide [34] Resistance exercise [35] Corticosteroids [36] Genetic interventions [37] Poor adherence, difficulty to carry out without assistance due to inherent frailty of sufferers Delays symptoms only, multiple known severe side effects [36] Large organ to treat. Need to target skeletal and cardiac muscle.…”
Section: Myopathiesmentioning
confidence: 99%
“…A common myopathy is sarcopenia [25] (age-related loss of muscle mass and strength); a disease associated with frailty and has a high incidence in the older population (Table 1). There are also numerous genetic diseases such as muscular dystrophies (MD) [26], for example, Duchene muscular dystrophy (DMD), and limb girdle MD.…”
Section: Myopathiesmentioning
confidence: 99%
“…Kutatá-sunk az elsőnek nem, csak az utóbbinak a preventív hatására mutatott rá. A prevalenciában jelentős különbségek vannak az egyes kutatások eredményei között: az Egyesült Király-ságban 7,8%-os prevalenciát becsültek [16]. Brazil, japán és koreai populációban 12-22% között mozgott a kimutatott gyakorisági adat [18,31,32].…”
Section: Megbeszélésunclassified
“…A hatékony intézkedések megtervezéséhez a sarcopenia patomechanizmusa mellett a sarcopeniával kapcsolatban álló, azt befolyásoló életmódbeli tényezők ismerete is szükséges. A korábbi kutatások otthon élő idősek körében vizsgál-ták a sarcopenia prevalenciáját, valamint azt, hogy az egészség-és életmódbeli tényezők hogyan függnek ösz-sze a sarcopenia gyakoriságával [8,[13][14][15][16][17][18][19]. Eddig azonban azt nem vizsgálták, hogy a tartós ellátást nyújtó idősotthonban élőknél van-e összefüggés a fenti ténye-zők és a sarcopenia előfordulása között.…”
unclassified